The morphology, molecular development and ecological function of pseudonectaries on Nigella damascena (Ranunculaceae) petals - Hong Liao (Nature Portfolio, 2020)
Interspecies interactions, including those between plants and pollinators, can involve deception. The authors characterize the molecular development of Nigella damascena pseudonectaries, and their adaptive function in attracting specific pollinators to concealed nectaries with visual cues.